Penyuluhan dan Pelatihan Konstruksi Rumah Tahan Gempa kepada Tukang Bangunan di Desa Buwun Mas, Kecamatan Sekotong, Kabupaten Lombok Barat - Adryan Fitrayudha; Heni Pujiastuti; Hafiz Hamdani; Nurul Hidayati; Ahmad Zarkasi; Aulia Muttaqin; Maya Saridewi Pascanawati; Isfanari Isfanari; Rajabi Mubarak; Intan Novianti; Feri Irawan; Chairil Anhar (Rengganis Jurnal Pengabdian Masyarakat, 2023)
The threat of an earthquake can occur anytime and anywhere. In 2018 the island of Lombok was shaken by an earthquake with a magnitude of 7.0 on the Richter scale at a depth of 15 km. One of the areas that were quite badly affected by the quake was Sekotong District, Buwun Mas Village, and West Lombok Regency. Records of damage to the local village government show that 45% of residents' houses were heavily damaged, 30% were moderately damaged, and 2% were lightly damaged. This service aims to provide education and training on the construction of earthquake-resistant houses based on the latest SNI seismic regulations for Buwun Mas Village builders to reduce risk due to earthquakes. The method used is to provide counseling and training to the masons and chief masons in the village of Buwun Mas. This activity was held on Saturday, 4 June 2022, and ran smoothly and in an orderly manner; during the implementation of the community service activities, the partners, in this case, the Buwun Mas Village government, the leaders and occupants of the Zainul Hafidz At-Taufiq Islamic Boarding School and the builders in Buwun Mas Village were very enthusiastically participated in counseling and training activities on earthquake resistant housing construction. This can be seen from the total number of participants reaching 54 people. This counseling and training activity is only for education and to increase the knowledge of the artisans in the village of Buwun Mas, Sekotong District.